The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpls.2021.766550
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Investigation of the NAC Transcription Factor Family in Miscanthus sinensis and Expression Analysis Under Various Abiotic Stresses

Abstract: The NAC transcription factor family is deemed to be a large plant-specific gene family that plays important roles in plant development and stress response. Miscanthus sinensis is commonly planted in vast marginal land as forage, ornamental grass, or bioenergy crop which demand a relatively high resistance to abiotic stresses. The recent release of a draft chromosome-scale assembly genome of M. sinensis provided a basic platform for the genome-wide investigation of NAC proteins. In this study, a total of 261 M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Collinearity analysis showed that there are 157 duplication events among oat NAC genes, comprising 146 segmental duplication events and 11 tandem duplication events, indicating that segmental duplication dominated oat gene expansion events. Similar results were reported for Miscanthus sinensis [21] and Triticum dicoccoides [23]. Gene duplication can be driven by DNA break repair.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Collinearity analysis showed that there are 157 duplication events among oat NAC genes, comprising 146 segmental duplication events and 11 tandem duplication events, indicating that segmental duplication dominated oat gene expansion events. Similar results were reported for Miscanthus sinensis [21] and Triticum dicoccoides [23]. Gene duplication can be driven by DNA break repair.…”
Section: Discussionsupporting
confidence: 84%
“…Compared with that in other plant species, the number of NAC genes identified in cultivated oat is relatively high. In most cases, differences in the number of NAC genes could be attributed to differences in the genome size of each species [21]. Therefore, the high number of NAC genes in oat is partly caused by the derivation of the cultivated hexaploid oat from the hybridization of three diploid ancestors, thus containing six sets of chromosomes (AA, CC, and DD subgenomes).…”
Section: Discussionmentioning
confidence: 99%
“…PCR reactions were carried out with triplicate. The relative expression of target genes was normalized to the internal reference gene ACTIN ( Unigene33024 ) [ 59 ] using the 2 −ΔΔCT method. Primers are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Britton & Rose [ 9 ], Juglans mandshurica Maxim. [ 10 ], Medicago sativa L. [ 11 ], Miscanthus sinensis Andersson [ 12 ], banana ( Musa acuminata Colla) [ 13 ], Oryza sativa L. [ 5 ], Populus trichocarpa Torr. & A.…”
Section: Introductionmentioning
confidence: 99%